Chemically stable two-dimensional MXene@UIO-66-(COOH)2 composite lamellar membrane for multi-component pollutant-oil-water emulsion separation. (15th September 2020) - He, Shuangjiang; Zhan, Yingqing; Hu, Jiaxin; Zhang, Guiyuan; Zhao, Shumei; Feng, Qingying; Yang, Wei
Abstract: Multi-component pollutant-oil-water emulsion from the fast-growing industry seriously threatens the human health and ecological environment, which poses a huge challenge to membrane technology. Recently, 2D MXene materials have shown promising and potential candidates for functional separation membranes. Herein, for the first time, a multitasking hierarchical MXene@UIO-66-(COOH)2 composite membrane supported on nylon 66 microporous substrate was designed via a facial strategy, which possessed high chemical stability and efficient multi-component pollutant-oil-water emulsion separation performance. The promising synergistic separation performance of various oil-in-water emulsions and dye, high antifouling resistance, and excellent recyclability of MXene@UIO-66-(COOH)2 composite membrane originated from the inherent hydrophilicity, low oil adhesion feature, and hierarchical intercalation structure of membrane. Furthermore, the chemically stable MXene@UIO-66-(COOH)2 composite membrane exhibited outstanding corrosion resistance under strong acid (3 M HCl), alkali (1 M NaOH) and salty (Saturated NaCl) solutions. Therefore, this work provides a powerful platform for designing stable and functional 2D membrane materials for multi-component pollutant-oil-water emulsion separation in harsh chemical environments. Graphical abstract: Image 1 Highlights: A multitasking 2D MXene@UIO-66-(COOH)2 composite lamellar membrane was designed via a facial strategy. The membrane showed promising synergistic separation performance for various oil-in-water emulsions and dye. The membrane possessed high antifouling resistance and excellent recyclability. The membrane possessed outstanding chemical stability and corrosion resistance in harsh chemical conditions.